PENGARUH BRAND IMAGE DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK IPHONE PADA MAHASISWA FKIP UNBARA ANGKATAN 2022-2023 - Shara Febria Charera; Novegya Ratih Primandari; Dahlia (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2025)
This study aims to examine the influence of Brand Image and Word of Mouth on the Purchase Decisions of iPhone smartphones among students of the Faculty of Teacher Training and Education (FKIP) at Baturaja University (UNBARA), Class of 2022-2023. The method used in this research is a quantitative method. The population consists of FKIP UNBARA students from the 2022-2023 academic years, with the sample selected through a purposive sampling technique, resulting in a total of 44 respondents. Data collection was conducted using online questionnaires via Google Forms. The data analysis technique employed was multiple linear regression analysis. The results of the partial data processing show that the t-value for Brand Image (X1) is 3.612, which is greater than the t-table value of 2.019, meaning that Brand Image has a positive and significant effect on Purchase Decisions. Similarly, the t-value for Word of Mouth (X2) is 3.508, which is greater than the t-table value of 2.019, indicating that Word of Mouth also has a positive and significant effect on Purchase Decisions. Furthermore, simultaneous testing (F-test) reveals that Brand Image and Word of Mouth together have a positive and significant impact on Purchase Decisions, as evidenced by an F-value of 29.367, which exceeds the F-table value of 3.23. The coefficient of determination (R2) is 0.589, indicating that Brand Image and Word of Mouth contribute 58.9% to Purchase Decisions, while the remaining 41.1% is influenced by other factors such as quality, service, and price.